Healthcare seeking behavior for back and Joint pain in rural Gadchiroli, India: A population-based cross-sectional study - Sona A Deshmukh; Yogeshwar V Kalkonde; Mahesh D Deshmukh; Anand A Bang; Abhay T Bang (Wolters Kluwer Medknow Publications, 2014)
Background: Musculoskeletal back and joint pain is common in rural agrarian communities in India. Objectives: To understand the healthcare seeking behavior for back and joint pain among adults in rural Gadchiroli, India. Materials and Methods: A cross-sectional survey of 315 randomly selected respondents from 84 villages between 30 and 60 years of age was conducted by community health workers (CHWs) between October 2010 and January 2011. Results: Among 280 respondents on whom good quality data were available, 215 (76.8%) respondents had back and/or joint pain in 6 months preceding the survey. A majority of the respondents with pain had sought care (170; 79.1%), mainly from private practitioners (116; 68.2%). Severe pain and inability to work were the reasons to seek care. Complete pain relief was considered the major indicator of an effective treatment. Injectable medications (127; 59.1%) and intravenous fluids (92; 42.8%) were considered highly effective; while about 50% were unaware of the role of physiotherapy and surgery for this problem. When asked about the preferred provider who should provide village level treatment of this problem, more than half (135; 62.8%) of the respondents chose a trained village health worker. Conclusions: A majority of the individuals with back and/or joint pain in rural Gadchiroli seek care, mainly from private practitioners. However, for the village-level treatment of this problem, respondents preferred a trained village level worker. High expectation of complete pain relief, preference for injectable medications, and low awareness about nonpharmacological modalities will be the major challenges while providing community level care for this problem.